Peculiarities of EPR spectra of methyl radicals in quench-condensed krypton films - Dmitriev, Yu.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2007)
Methyl radicals are trapped in the solid Kr film by simultaneous condensation of gaseous Kr and the products of the gas discharge in CH4 doped Kr on the low temperature (4.2 K) substrate located at the center of the microwave cavity. The observed EPR spectrum is a superposition of broad-line and narrow-line series. At a low resonance microwave power, the latter one consists of four hyperfine components with nearly equal intensities, and shows small axial anisotropy of both g- and A-tensors. At a sufficiently large power, two central narrow lines split so that the narrow-line series takes an appearance recorded elsewhere for CH3 in Ar at higher temperatures above 12 K. Simultaneously, the intensity of two central broad lines increases dramatically while the outer components become saturated. The possible explanation is discussed.